Environmental scanning as information seeking and organizational learning (Information Research: An International Electronic Journal)
Environmental scanning is the acquisition and use of information about events, trends, and relationships in an organization's external environment, the knowledge of which would assist management in planning the organization's future course of action. Depending on the organization's beliefs about environmental analyzability and the extent that it intrudes into the environment to understand it, four modes of scanning may be differentiated: undirected viewing, conditioned viewing, enacting, and searching. We analyze each mode of scanning by examining its characteristic information needs, information seeking, and information use behaviours. In addition, we analyze organizational learning processes by considering the sensemaking, knowledge creating and decision making processes at work in each mode.